Current State of Vascular Resections in Pancreatic Cancer Surgery - Thilo Hackert; Lutz Schneider; Markus W. Büchler (Gastroenterology Research and Practice)
Pancreatic cancer (PDAC) is the fourth leading cause of cancer-related mortality in the Western world and, even in 2014, a therapeutic challenge. The only chance for long-term survival is radical surgical resection followed by adjuvant chemotherapy which can be performed in about 20% of all PDAC patients by the time of diagnosis. As pancreatic surgery has significantly changed during the past years, extended operations, including vascular resections, have become more frequently performed in specialized centres and the border of resectability has been pushed forward to achieve a potentially curative approach in the respective patients in combination with neoadjuvant and adjuvant treatment strategies. In contrast to adjuvant treatment which has to be regarded as a cornerstone to achieve long-term survival after resection, neoadjuvant treatment strategies for locally advanced findings are currently under debate. This overview summarizes the possibilities and evidence of vascular, namely, venous and arterial, resections in PDAC surgery.